Gendered Temporalities in the Early Modern World - Wiesner, Merry E. (2018)
Is time gendered? This international, interdisciplinary anthology studies the early modern era to analyse how material objects express, shape, complicate, and extend human concepts of time and how people commemorate time differently. It examines conceptual aspects of time, such as the categories women and men use to define it, and the somatic, lived experiences of time ranging between an instant and the course of family life. Drawing on a wide array of textual and material primary sources, this book assesses the ways thatgender and other categories of difference affect understandings of time.